Gingerly Yours: A feasibility study on ginger cultivation in Bacoor, Cavite - Capili, Renzo Miguel B., Formalejo, Sophia Izabelle B., Galoz, Joshuea A., Matuguina, Kyla Catrina S., Merilles, Ma. Maixne Naomi G., Nakpil, Jian Justine L., Nitura, Louisse Anthony A. 4 0 16; 5
u
Feasibility Study: (BSBA major in Business Economics) - Pamantasan n g Lungsod ng Maynila, 2024
Keywords: 2 -- 0; 6; 20; 20; 2